Industrial clusters
1 online resource.
Keywords: "Industrial Clusters shows the latest state of knowledge on the topic of industrial clusters, with a particular focus on clustering in the UK, and brings together a chronological coverage of the phenomenon. This set of original essays by a group of leading business and industrial historians offers fresh perspectives about clusters and clustering. A primary emphasis of the collection is how knowledge is generated and disseminated across a cluster, and whether these processes stimulated innovation and consequently longer-term sustainability. This analysis also prompts questions about which unit of analysis to examine, from the entrepreneurs and firms they created through to the industry as a whole and district in which they are located, or whether one should look outside the region for explanatory factors. Covering regions as diverse as North Wales, the Scottish Highlands, the City of London, the Potteries, Sheffield and Lancashire, the essays have been channelled to provide a detailed understanding of these issues. The editors have also provided a challenging Conclusion that suggests a new research agenda that could well unravel some of the mysteries associated with clustering. This edited collection will be of interest to international researchers, academics, and students in the fields of business and management history, innovation, industrialisation, and clusters"--